2019
DOI: 10.3390/antibiotics8030106
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-Resistant Septicemia in Pediatric Oncology Patients Associated with Post-Therapeutic Neutropenic Fever

Abstract: Death in cancer patients can be caused by the progression of tumors, their malignity, or other associated conditions such as sepsis, which is a multiphasic host response to a pathogen that can be significantly amplified by endogenous factors. Its incidence is continuously rising, which reflects the increasing number of sick patients at a higher risk of infection, especially those that are elderly, pediatric, or immunosuppressed. Sepsis appears to be directly associated with oncological treatment and fatal sept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
0
10
0
1
Order By: Relevance
“…More recently, there has been re-emergence of gram-negative bacteria, in pediatric oncology patients. 5 Inonestudy, in a pediatric oncology unit, 74 (58%) cultures yielded Gram-negative bacilli, 51 (40%) were positive for Gram-positive cocci, and 3 (2%) grew fungi. 3 Another study found 69% positive blood cultures caused by gram-negative bacteria, 28.8% by gram-positive organisms, and 2.2% by fungi.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, there has been re-emergence of gram-negative bacteria, in pediatric oncology patients. 5 Inonestudy, in a pediatric oncology unit, 74 (58%) cultures yielded Gram-negative bacilli, 51 (40%) were positive for Gram-positive cocci, and 3 (2%) grew fungi. 3 Another study found 69% positive blood cultures caused by gram-negative bacteria, 28.8% by gram-positive organisms, and 2.2% by fungi.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Staphylococcus aureus, Enterococcus spp., Enterobacteriaceae (other than Salmonella and Shigella), Pseudomonas aeruginosa, and Acinetobacter spp. [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…To classify these microorganisms according to the degree of resistance and acquired resistance profiles, a group of experts in the field of antimicrobial resistance in joint work with the European Center for the Prevention of Diseases and Control (ECDC) and the CDC established the definitions and characteristics among resistant bacteria: multidrug-resistant (MDR), extensively drug-resistant (XDR), and pan drug-resistant (PDR) bacteria [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations